2006
DOI: 10.1089/jop.2006.22.176
|View full text |Cite
|
Sign up to set email alerts
|

Brimonidine 0.2% Versus Brimonidine Purite 0.15%: Prophylactic Effect on IOP Elevation After Nd:YAG Laser Posterior Capsulotomy

Abstract: Brimonidine 0.2% and brimonidine Purite 0.15% have similar efficacy in the prevention of IOP elevation after Nd:YAG laser posterior capsulotomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 27 publications
0
11
0
Order By: Relevance
“…IOP elevations of ‡ 5 mmHg occurred in 7.3% of patients, and IOP elevations of ‡ 10 mmHg occurred in 2.4% of patients treated with brimonidine. In another study, Yeom et al 27 have demonstrated that brimonidine 0.2% and brimonidine purite 0.15% had a similar efficacy for prevention of IOP elevation after Nd:YAG laser posterior capsulotomy. IOP elevations of ‡ 5 mmHg were observed in 5.7% of patients and elevations of IOP ‡ 10 mmHg were observed in 2.9% of patients treated with brimonidine.…”
Section: Discussionmentioning
confidence: 96%
“…IOP elevations of ‡ 5 mmHg occurred in 7.3% of patients, and IOP elevations of ‡ 10 mmHg occurred in 2.4% of patients treated with brimonidine. In another study, Yeom et al 27 have demonstrated that brimonidine 0.2% and brimonidine purite 0.15% had a similar efficacy for prevention of IOP elevation after Nd:YAG laser posterior capsulotomy. IOP elevations of ‡ 5 mmHg were observed in 5.7% of patients and elevations of IOP ‡ 10 mmHg were observed in 2.9% of patients treated with brimonidine.…”
Section: Discussionmentioning
confidence: 96%
“…Since we instilled one drop of brimonidine 0.15%, 30 minutes preoperatively to all the eyes, we did not observe IOP rise in any patients. It was shown that pre‐operative topical brimonidine administration prevents acute IOP rise after the laser capsulotomy . We used low cumulative energy amounts during laser sessions and this would have an impact on the low IOP levels after the capsulotomy.…”
Section: Discussionmentioning
confidence: 99%
“…[1213] In a study by Gartaganis et al ., a significant mean percent reduction in IOP was found after 0.2% brimonidine instillation 1 h pre capsulotomy and immediately post capsulotomy. However in the present study, when one drop of 0.2% brimonidine was instilled 1 hour pre-capsulotomy and immediately after Nd-YAG laser capsulotomy, IOP elevations were prevented.…”
Section: Discussionmentioning
confidence: 99%